Minimum inhibition concentration and anti-fungal contact time of quaternary ammonium and ethylenediaminetetraacetic acid (EDTA) mixture towards Candida Albicans isolate - Yunita, Elizabeth; Hardjawinata, Karlina; Dewi, Warta (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
The aim of this study is to determine the Minimum Inhibitory Concentration (MIC) and the exposure time of the combination of quaternary ammonium compound with EDTA towards Candida albicans isolates from the 5 upper acrylic removable complete dentures. This experimental laboratory study was conducted based on a serial dilution of the combination of quaternary ammonium compound with EDTA towards Candida albicans in 3 replications and statistically analyzed according to Kruskal-Wallis method. The result showed that the MIC of the combination of quaternary ammonium compound with EDTA towards Candida albicans was in 1/8000 concentration with minimum 8 hours exposure time. This study concluded that the combination of quaternary ammonium compound with EDTA had an antifungal activity towards Candida albicans at 1/8000 concentration in 8 hours exposure time.